Menentukan Penjadwalan Maintenance Mesin Finish Mill Dengan Metode FMEA Di PT Semen Indonesia (PERSERO) Tbk - Abid, Ahmad Muttaqi Alfirdaus; Ashari, Faisal (Jurnal Teknologi dan Manajemen Sistem Industri, 2022)
PT Semen Indonesia (PERSERO) Tbk is a cement producing company in Tuban, so problems often occur in theproduction system including damage to the finish mill machine components. The machine components that are oftendamaged are Grinding tables, Tires, Reducer separators, Rockerarms, Bucket Chains, Seals, Shafts. The finish millmachine is the last area in the cement production process. The result of the final grinding in the form of cement isstored in cement storage silos. If maintenance is carried out on a scheduled basis, damage and production failurescan be minimized. The purpose of this industrial practical work is to schedule maintenance for finish mill machinesusing the FMEA method. The data collection method used was direct observation and interviews with theresponsible department in the finish mill machine area. From the results of industrial practical work carried out, itis known that machine maintenance is carried out with an overhaul system every few years. It is recommended toschedule maintenance for finish mill machines such as cleaning, replacement, lubrication so that components do notoften fail and damage during the production process.